2019
DOI: 10.1007/s13132-019-00594-4
|View full text |Cite|
|
Sign up to set email alerts
|

Democracy and Economic Growth: a Literature Review

Abstract: Given the importance of the joint analysis of the economic and political process, several researchers have examined the effect of the political regime on economic growth and development. The great majority of these researchers are crystallized on the assessment of the economic impact of a democratic political system in relation to an autocratic political regime. The aim of this review is to analyze the existing theoretical literature that underlines the effects of a democratic political system on economic grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 82 publications
1
14
0
2
Order By: Relevance
“…Their interdependence is mainly observed through the following dilemmas: Does (and to what extent) democracy stimulate or limit faster economic growth? (Ghardallou & Sridi, 2020) 3. Stringency Index is a composite measure based on nine response indicators including school closures, workplace closures, and travel bans, rescaled to a value from 0 to 100 (100 = strictest).…”
Section: Sources Of Data and Explanation Of Variables In The Modelmentioning
confidence: 99%
“…Their interdependence is mainly observed through the following dilemmas: Does (and to what extent) democracy stimulate or limit faster economic growth? (Ghardallou & Sridi, 2020) 3. Stringency Index is a composite measure based on nine response indicators including school closures, workplace closures, and travel bans, rescaled to a value from 0 to 100 (100 = strictest).…”
Section: Sources Of Data and Explanation Of Variables In The Modelmentioning
confidence: 99%
“…The literature on the relationship between democracy and economic growth is composite and evergrowing. A plethora of research has examined the effect of a political regime on economic growth and development, with the major focus being on the economic impact of a democratic political system in contrast to an autocratic one (Ghardallou & Sridi, 2019). Studies that have enquired into this relationship found a multitude of causality (Brunetti, 1997).…”
Section: Review Of Past Empirical Studiesmentioning
confidence: 99%
“…A more recent example is the Arab world uprisings during 2011 where the political regimes were shaken along with the economy. Analysts at the time predicted a top-down inversion of institutional order would induce economic prosperity, or, at the very least, shed a richer light on the fundamental relationship between the socioeconomic governing mechanisms and economic development (Ghardallou & Sridi, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the ability of the democratic government to manage conflicts strengthens the protection of property rights under a democratic regime. Therefore, by offering investors the necessary guarantees for the protection of their rights, democracy contributes to the development of capital markets relative to banks (Clague et al, 1996; Ghardallou, 2016, Ghardallou & Sridi, 2019; North & Weingast, 1989).…”
Section: Literature Reviewmentioning
confidence: 99%